Implications of the selective management system on the management of the hill forests of Peninsular Malaysia. - Universiti Putra Malaysia (Universiti Pertanian Malaysia, 1987)
The paper discusses the two requirements of the Selective Management System (SMS) as applied to the hill forests of Peninsular Malaysia : the need for economic cuts and the necessity of leaving sufficient advance regeneration in the residual stands to ensure adequate commercial timber volumes at subsequent harvests. Current guidelines expect a minimum harvest of 35 to 40 cubic m/ha every 25 to 30 years by specifying minimum cutting limits of 50 cm and 45 cm for diptrerocarp and non-dipterocarp species, respectively. The guidelines specify that the residual stands should contain a minimum of 32 sound stems of commercial species in the 30-45 cm dbh class or its equivalence in the whole range of tree sizes in the residual stands. A stem greater than 45 cm dbh is equivalent to 2 stems in the 30-45 cm dbh class, and a stem in the 15-30cm dbh class has an equivalent value of 1/3. The percentage of the number of dipterocarp stems greater than 30 cm dbh in the residual stands must be the same as or higher than that in the original stand. Implementation of the SMS is seen as balancing what is to be removed in the immediate harvest and what is to be left for future harvests. The implications on harvest volumes in the current and subsequent harvest and on the continued productivity of the forest are discussed.